The human right to liberty and Brazilian abortion practices - Tonetto, Milene (Revista Bioética, 2018)
The aim of this paper is to justify women’s right to abortion in the first trimester of pregnancy. Considering human rights as the protection of our normative agency or personhood, this paper will argue that human rights cannot be extended to human embryos and foetuses. In the first trimester of pregnancy, the moral status of the foetus is not sufficient to overcome the woman’s right to the freedom to control her own body. There may be, however, moral considerations other than human rights that could restrict abortions after the first trimester of pregnancy. In order to protect human personhood and the most fundamentally accepted human rights – the rights to freedom, life, health and security of the body – countries like Brazil should decriminalize abortion in the first trimester of pregnancy and provide access to safe abortions through the public health care system.